Improving Morpho-Physiological Indicators, Yield, and Water Productivity of Wheat through an Optimal Combination of Mulching and Planting Patterns in Arid Farming Systems - Salah El-Hendawy; Bazel Alsamin; Nabil Mohammed; Yahya Refay (Agronomy, 2023)
Mulching practices (M), which conserve soil water and improve water productivity (WP), are receiving increasing attention worldwide However, so far, little attention has been given to investigating the effects of the integrations of mulching and planting patterns (IMPPs) on spring wheat performance under arid regions conditions. A two-year field study was conducted to compare the effects of eight IMPPs on growth parameters at 80 and 100 days after sowing (DAS), growth indicators, physiological attributes, grain yield (GY), and WP of wheat under adequate (1.00 ET) and limited (0.50 ET) irrigation conditions. The IMPPs included three planting patterns (PPs), that is, flat (F), raised-bed (RB), and ridge–furrow (RF), in combination with three M, that is, no-mulch (NM), plastic film mulch (PFM), and crop residues mulch (CRM). The results indicated that PPs mulched with PFM and CRM significantly increased growth indicators, different growth parameters, physiological attributes, GY, and WP by 6.9–39.3%, 8.2–29.2%, 5.2–24.9%, 9.9, and 11.2%, respectively, compared to non-mulched PPs. The F and RB patterns mulched with CRM were more effective in improving growth parameters at 100 DAS (2.7–13.6%), physiological attributes (0.2–20.0%), GY, and WP (9.7%) than were the F and RB patterns mulched with PFM under 1.00 ET, while the opposite was true under 0.50 ET conditions. Although the RFPFM failed to compete with other IMPPs under 1.00 ET, the values of different parameters in this PP were comparable to those in F and RB patterns mulched with PFM, and were 1.3–24.5% higher than those in F and RB patterns mulched with CRM under 0.50 ET conditions. Although the RFNM did not use mulch, the values of different parameters for this PP were significantly higher than those of F and RB patterns without mulch. Irrespective of irrigation treatments, the heatmap analysis based on different stress tolerance indices identified the different PPs mulched with PFM as the best IMPPs for the optimal performance of wheat under arid conditions, followed by PPs mulched with CRM. The different growth indicators exhibited second-order and strong relationships with GY (R2 = 0.78 to 0.85) and moderate relationships with WP (R2 = 0.59 to 0.79). Collectively, we concluded that using PPs mulched with CRM is the recommended practice for achieving good performance and production for wheat under adequate irrigation, whereas using PPS mulched with PFM is recommended as a viable management option for sustainable production of wheat and improving WP under limited irrigation in arid countries.